الهمّ في الشعر الجاهليّ - أحمد عدنان محمد; عثمان مازن أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يسعى هذا البحث إلى الكشف عن ملامح الهمّ ودلالاته المتعددة، والأسباب التي أدت إلى تشكله، ويحاول كشف صوره، وكيفية الإحالة عليه عند الشعراء الجاهليّين في صورهم، وما كابدوه من لواعج الفقد التي أذهبت كثيراً من متع حياتهم. ومن يقرأ الشعر الجاهليّ بتأنٍّ، يمكنه أن يلاحظ – بغير عناء كبير – مسحة من الحزن مرتسمة حتى على أكثر لوحاته إشراقاً، ليس لأنّ الشعراء أغرموا بالحزن وبالتعبير عنه، بل لأنهم وقفوا وجهاً لوجه أمام الحقيقة الخالدة في الحياة، وهي الموت الذي كان يهدم كل شيء، ويسلب منهم كل ما أحبوه. This research studies the types of ’ subdual’ , its significances and the reasons which made it. It also tries to show its images and how the Pre-Islamic poets use it in their poems and what they suffer going through loss and concerns, so as a result of that they miss enjoying life. Through reading the pre-Islamic poetry carefully, you can easily feel the sadness even in the ones with no sad images. All of that because the poets faces the immortal reality of life, and not because of their tending to sadness and describing it. That reality is ’ death’ which destroys everything and takes everything they love.